Genetic variability and correlation analysis of exotic bread wheat accessions under early sown, irrigated and high fertility conditions - Prasad, S.V. Sai; Patidar, Manohar; Ambati, Divya; Singh, J. B.; Sharma, Brijesh; Tiwari, Dusyant; Patidar, C. P.; Malviya, Prakash (Annals of Agricultural Research, 2016)
Exotic bread wheat genotypes (132) received from CIMMYT, Mexico along with 3 check varieties were evaluated for 2 years under early sown irrigated and high fertility conditions to identify genotypes for coping with contemporary and projected climate extremes; and to estimate variability parameters, distribution and correlations for grain yield and its contributing traits. Significant genotypic differences were observed for all the traits studied indicating considerable amount of variation among genotypes for each character. High to moderate heritability coupled with high to moderate genetic advance as percentage of mean was exhibited for 5 traits viz., days to flowering, days to maturity, plant height, 1000 grain weight and spike length, which indicate that predominance of additive gene action in the expression of these characters and consequently greater chance of improving these traits through simple selection. No. of tillers/m, biomass/plot, harvest index and grain yield/plot showed low heritability along with low genetic advance, which suggested that the presence of non-additive gene action and hence, improvement of these traits could be difficult through direct selection. Grain yield/plot showed significantly positive correlation with days to heading, plant height, spike length, no. of tillers/m, 1000 grain weight, biomass/plot and harvest index. As a whole, genotypes viz., 45th IBWSN 1315, 29th SAWSN 3125 and 30th SAWSN 3036 showed high grain yield along with superior yield contributing traits, hence, they can be utilized as a potential donors for improving grain yield in our wheat varieties under early sown, irrigated and high fertility conditions